2009
DOI: 10.1080/02713680903056391
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Role of Extracellular Phospholipase B ofCandida albicansas a Virulent Factor in Experimental Keratomycosis

Abstract: PLB can play a role as a virulent factor in triggering fungal invasion in corneas immediately after fungal adherence by decomposing membrane phospholipids and leading to cell lysis. However, its virulent effect does not appear to be as critical as in the hematogenous model of disseminated candidiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…experimented with corneal stroma and reported that PLB comes into action immediately after fungal adherence by decomposing the phospholipid of cell membranes and leading to cell lysis. [ 11 ] In Candida , phospholipase activity is concentrated at the growing tip of the pseudohyphae. Ibrahim et al .…”
Section: Discussionmentioning
confidence: 99%
“…experimented with corneal stroma and reported that PLB comes into action immediately after fungal adherence by decomposing the phospholipid of cell membranes and leading to cell lysis. [ 11 ] In Candida , phospholipase activity is concentrated at the growing tip of the pseudohyphae. Ibrahim et al .…”
Section: Discussionmentioning
confidence: 99%
“…The role of extracellular phospholipases, particularly phospholipase B (PLB), as potential virulence factors for pathogenic fungi, including Candida albicans [ 4 , 5 ] , Cryptococcus neoformans [ 6 - 10 ], and Aspergillus fumigatus [ 11 ] has been reported, although the underlying mechanism has yet to be elucidated. Extracellular phospholipase activities have also been detected in in-vitro cultures of P. brasiliensis [ 12 ], and PLB has been postulated as a potential virulence factor for this pathogen by in-silico analysis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%